Effects of heat hardening on life parameters and thermostability of Bradysia odoriphaga larva and adults. (19th November 2021) - Zhu, Guodong; Zhao, Haipeng; Xue, Ming; Qu, Cheng; Liu, Shouzhu
Abstract: Environmental temperature is an important factor restricting insect population dynamics. Due to the ongoing global warming, interest in the impact of heat stress on insects has grown. High temperature in summer is a key barrier for Bradysia odoriphaga (Diptera: Sciaridae), a devastating vegetable pest o in China. It is well known that moderate thermal hardening can enhance the thermotolerance of many insects, which is beneficial for adaptation to environmental thermal stress. In order to determine whether heat hardening was beneficial for B . odoriphaga to adapt to high summer temperatures, we studied the biological performance, antioxidant responses and hsp70 and hsp90 expression of B . odoriphaga 4th instar larvae and adults after pre‐exposure to mild heat hardening temperatures (30–36°C). Mild heat hardening (32–36°C) enhanced the larval thermal tolerance to extreme heat stress. However, life parameters were significantly inhibited, development was delayed, longevity was shortened, and fecundity was decreased. Mild heat hardening (30–34°C) caused serious adverse effects on life parameters and less enhancement of heat resistance for 4th instar larvae. Mild heat hardening at 36°C weakened the heat tolerance of adults. The activity of four antioxidant enzymes in B . odoriphaga changed dramatically after heat hardening at 32–36°C. During recovery at 25°C, catalase (CAT), peroxidase (POD) and glutathione‐ S ‐transferase (GST) in tested larvae maintained successive higher activities after heat hardening. Simultaneously, the expression levels of hsp70 and hsp90 increased significantly after thermal hardening. Higher expression levels were also detected in larvae, pupae and adults after 48 hr recovery at 25°C. Overall, mild heat hardening played an important role in heat tolerance plasticity of B . odoriphaga larvae, and the antioxidant system and hsp70 and hsp90 genes were extremely relevant to this adaptation process.